Compositional Control in 2D Perovskites with Alternating Cations in the Interlayer Space for Photovoltaics with Efficiency over 18%. Issue 44 (15th September 2019) - Luo, Tao; Zhang, Yalan; Xu, Zhuo; Niu, Tianqi; Wen, Jialun; Lu, Jing; Jin, Shengye; Liu, Shengzhong (Frank); Zhao, Kui
Abstract: 2D perovskites stabilized by alternating cations in the interlayer space (ACI) represent a very new entry as highly efficient semiconductors for solar cells approaching 15% power conversion efficiency (PCE). However, further improvements will require understanding of the nature of the films, e.g., the thickness distribution and charge‐transfer characteristics of ACI quantum wells (QWs), which are currently unknown. Here, efficient control of the film quality of ACI 2D perovskite (GA)(MA) n Pb n I3 n +1 (〈 n 〉 = 3) QWs via incorporation of methylammonium chloride as an additive is demonstrated. The morphological and optoelectronic characterizations unambiguously demonstrate that the additive enables a larger grain size, a smoother surface, and a gradient distribution of QW thickness, which lead to enhanced photocurrent transport/extraction through efficient charge transfer between low‐ n and high‐ n QWs and suppressed nonradiative charge recombination. Therefore, the additive‐treated ACI perovskite film delivers a champion PCE of 18.48%, far higher than the pristine one (15.79%) due to significant improvements in open‐circuit voltage and fill factor. This PCE also stands as the highest value for all reported 2D perovskite solar cells based on the ACI, Ruddlesden–Popper, and Dion–Jacobson families. These findings establish the fundamental guidelines for the compositional control of 2D perovskites for efficient photovoltaics. Abstract : An efficient control of the film quality and thickness distribution of alternating cations in the interlayer space of 2D perovskite (GA)(MA) n Pb n I3 n +1 (〈 n 〉 = 3) quantum wells via incorporation of methylammonium chloride as an additive is demonstrated. The optimized device leads to more efficient charge transport and suppressed nonradiative charge recombination. Consequently, the optimized perovskite solar cell delivers an efficiency of 18.48%.